Lichens of Pueblo Libre, an Andean locality from Cordillera Negra (Huaylas, Ancash, Perú) - Ramírez, Ángel (2005)
In this paper we report the lichens of Pueblo Libre, an Andean locality, (09º05’30’’ - 09º10’15’’ S and 77º47’30’’ - 77º52’50’’ W) in Huaylas, Ancash, Peru. Surveys were made at 2200 to 4450 m of elevation. In all 38 species, 29 genera and 17 families, besides one imperfect taxon are are reported. A key of family, genera and species is included. Morphological and anatomical features are described for each species, including its chemical reaction, habitat and vouchers.